NON FORMAL EDUCATION IN DESIGN FIELD - M. Olărescu, Alin; Gronegger, Thomas; Bartha, Biborka; Cionca, Marina; Muscu, Ioan (Innovation in Woodworking Industry and Engineering design, 2018)
In this paper several guidelines and methodological approaches for non-formal education in the field of design are presented. The research is based on eight years experiences of the authors in organizing and guiding one week of international (Romanian and Austrian students and teachers) design workshops in Romania.